Patient involvement in resident assessment within the Competence by Design context: a mixed-methods study - Moreau, Katherine; Eady, Kaylee; Jabbour, Mona (Canadian Medical Education Journal, 2019)
Background: Patients can contribute to resident assessment in Competence by Design (CBD). This study explored the extent, nature, as well as the facilitators and hindrances of patient involvement in resident assessment within and across Canadian specialty/sub-specialty/special programs that are transitioning or have transitioned to CBD. Methods: We used a two-phase sequential explanatory mixed-methods design. In Phase 1, we surveyed program directors (PDs). In Phase 2, we interviewed PDs from Phase 1. Results: In Phase 1, 63 (62.4%) respondents in the CBD preparation stage, do not know if patients will be involved in resident assessment, 21 (20.8%) will involve patients, and 17 (16.8%) will not involve patients. Of those in the field-testing or implementation stages, 24 (72.7%) do not involve patients in resident assessment, five (15.2%) do involve patients, and four (12.1%) do not know if they involve patients. In Phase 2, 12 interviewees raised nine factors that facilitate or hinder patient involvement including, patients’ interests/abilities, guidelines/processes for patient involvement, type of Entrustable Professional Activities, type of patient interactions in programs, and support from healthcare organizations. Conclusion: Patient involvement in resident assessment is limited. We need to engage in discussions on how to support such involvement within CBD.